World without end [compact disc, unabridged] - Follett, Ken (Penguin Audio, 2007)
In the town of Kingsbridge, a Gothic cathedral and the priory are at the center of a web of love and hate, greed and pride, ambition and revenge. Proponents of the old ways fiercely battle those with progressive minds, as the Black Death captures the city.